Advances in social network analysis research in the social and behavioral sciences - Galaskiewicz Joseph; Wasserman Stanley (New Delhi Sage, 1994)
Social network analysis, a method for analyzing relationships between social entities has expanded over the last decade as new research has been done in this area. How can these new developments be applied effectively in the behavioral & social sciences
Keywords: Behavioral sciences; Research methods; Social networks; Social sciences-research